Pharmacological Modulation of HIF-1α in The Cerebral Cort1ex of Rats after Chronic Prenatal Hypoxia - Aliyeva, O. G.; Belenichev, I. F.; Popazova, O. O.; Zidrashko, G. A.; Алієва, Олена Геннадіївна; Бєленічев, Ігор Федорович; Попазова, Олена Олександрівна; Зідрашко, Галина Анатоліївна (My University, 2022)
Despite the significant advances in modern medicine, the problem of perinatal hypoxic CNS damage in children occupies one of the leading places in modern neonatology. Hypoxic damage to the fetal brain is the cause of delayed psycho-linguistic and motor development, mental insufficiency, movement disorders, cerebral palsy, disability and severe cases of neonatal mortality.
Keywords: CNS; prenatal hypoxia; endogenous neuroprotection; HIF-1a